The Bulgarian After-school Service System: Evolution, Mechanisms, and Pedagogical Implications for Global Educational Equity - Wu, Lin; Xu, Meijie (Journal of Educational Research and Policies, 2025)
Following nearly eight decades of systemic evolution, Bulgaria’s modern after-school service framework has developed into a well-established system characterized by innovative goal integration, diversified agent synergy, reasonable content layering, and impressive spatial extension, which has demonstrated significant efficacy in enhancing educational equity and social inclusion. This study conducts a comprehensive analysis of the evolutionary trajectory, multi-dimensional operational mechanisms, and pedagogical implications of this after-school service system, drawing on an exhaustive review of governmental policy texts, national statistical databases, and peer-reviewed empirical studies. The findings offer pedagogical implications for cross-national policy adaptation in educational equity enhancement.